Hollow monocrystalline silicalite‐1 hybrid membranes for efficient pervaporative desulfurization. Issue 1 (29th September 2018) - Pan, Fusheng; Li, Weidong; Zhang, Ye; Sun, Jie; Wang, Meidi; Wu, Hong; Jiang, Zhongyi; Lin, Ligang; Wang, Baoyi; Cao, Xingzhong; Zhang, Peng
Abstract : Hollow monocrystalline silicalite‐1 (HMS) nanoparticles were successfully synthesized and firstly incorporated into poly(ether‐ block ‐amide) (Pebax) to prepare hybrid membranes. The uniformly dispersed HMS in Pebax matrix interrupt the crystalline region and optimize the free volume property. The micropores on the HMS shell enhance the selectivity because of sieving effect, whereas the inner cavity benefits the rapid diffusion of penetrant and elevates the flux. When the content of HMS (200 nm) is 20 wt %, the hybrid membrane possesses a permeation flux of 20.63 kg/(m 2 h) and an enrichment factor of 6.11 (82% and 23% higher than that of Pebax membrane, respectively), which surpass the upper bound of the state‐of‐the‐art reported polymeric membranes. Moreover, the hybrid membranes display the remarkable antiswelling and long‐term operation stability. This is a step forward in fabricating the hybrid membranes with superior separation performance by incorporating porous fillers with hollow structure. © 2018 American Institute of Chemical Engineers AIChE J, 65: 196–206, 2019